ANALYSIS OF THE SOCIAL MEDIA MARKETING EFFECTS ON BRAND LOYALTY MEDIATED BY BRAND AWARENESS AND PURCHASE INTENTION - Cristie Yen, Selfia; Fahlevi, Renza (Jurnal Ilmiah Bisnis dan Ekonomi Asia, 2023)
According to Market Study Report in 2020, global sportswear sales are expected to reach USD 308.3 billion at a CAGR of 4.6% in 2025. Indonesia is considered one of the potential markets for the sportswear industry due to its large population. This study examines the Purchase Intention of consumers for sportswear using Social Media Marketing, Brand Loyalty, and Brand Awareness. The findings of this study will assist sportswear retailers in developing sales-boosting Social Media Marketing strategies. Research data were collected by distributing questionnaires to 160 consumers who had purchased sportswear and had access to social media. The purposive sampling technique was used to identify the respondents. The smartPLS 3.0 was used to process the data application and the Structural Equation Model (SEM) Partial Least Square statistical method. The findings revealed that social media marketing positively and significantly influenced brand loyalty. Simultaneously, Brand Awareness and Purchase Intention mediated the relationship between Social Media Marketing and Brand Loyalty.